2009
DOI: 10.1007/s11626-008-9166-1
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining hepatocyte differentiation in vitro through co-culture with hepatic stellate cells

Abstract: Primary hepatocytes lose their differentiated functions rapidly when in culture. Our aim was to maintain the differentiated status of hepatocytes in vitro by means of vital hepatic stellate cells (HSCs), their soluble and particulate factors and lipid extracts. Hepatocytes were placed into collagen-coated culture dishes in the presence of HSCs at different ages of pre-culture, with or without direct cell to cell contacts, at different cell ratios and in monoculture with cellular HSC components in place of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…We chose Hfsc as a co-culture component because of their established roles in liver homeostasis and regeneration by either direct cell contact or the secretion of soluble growth factors that support hepatocytes and ECM proteins [ [32][33][34][35]. Furthermore, Hfsc that are pre-cultured for 1 to 2 d before being co-cultured with hepatocytes exerted beneficial effects on hepatocyte function, structure, and differentiation [33]. Because one stellate cell spans two to three hepatocytes in vivo [36], we seeded Hfsc 2 d before the infusion of Hfh at a ratio BARAKAT ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…We chose Hfsc as a co-culture component because of their established roles in liver homeostasis and regeneration by either direct cell contact or the secretion of soluble growth factors that support hepatocytes and ECM proteins [ [32][33][34][35]. Furthermore, Hfsc that are pre-cultured for 1 to 2 d before being co-cultured with hepatocytes exerted beneficial effects on hepatocyte function, structure, and differentiation [33]. Because one stellate cell spans two to three hepatocytes in vivo [36], we seeded Hfsc 2 d before the infusion of Hfh at a ratio BARAKAT ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Riccalton-Banks compared the functionality of hepatocyte-only and hepatocyte-stellate (2:1 ratio) spheroids (Riccalton-Banks, 2002) and found that the co-cultured spheroids remained functional (in terms of albumin secretion and cytochrome P-450 enzyme activity) for nearly two months, compared to just over one month for the hepatocyte-only spheroids. Krause et al (2009) reported improved functionality (measured by phosphoenolpyruvate carboxykinase (PCK) activity) in short-term (48 hours) 2D co-cultures. The improvement was greatest when the culture arrangements allowed for physical contact between the two cell types, and a hepatocyte : stellate ratio of 1:4 was used.…”
Section: Discussionmentioning
confidence: 99%
“…When hepatocytes and stellate cells are co-cultured, cell aggregates form more rapidly and retain liver-specific functions (such as albumin production and cytochrome P450 activity) for a longer period than when the hepatocytes are cultured alone (Krause et al, 2009;Riccalton-Banks et al, 2003;Riccalton-Banks, 2002;Thomas et al, 2005). One mechanism that may contribute to enhanced aggregation is chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is important to recognize the role of the hepatocellular microenvironment during the process of stem cell therapy. There is accumulating evidence suggesting that cocultures of hepatocytes and non-parenchymal cells, including hepatic stellate cells [53][54][55] and endothelial cells [56,57], greatly improve hepatocyte functionality in vitro. Manipulation of the in vitro culture substrate using different extracellular matrix components or their synthetic chemical mimics also leads to improved and prolonged biological function [54,58,59].…”
Section: Modalities Of Liver Stem Cell Therapymentioning
confidence: 99%